Existence of positive solutions for a system of semipositone coupled discrete boundary value problems. Issue 4 (3rd April 2019) - Henderson, Johnny; Luca, Rodica
ABSTRACT: We study the existence of positive solutions for a system of nonlinear second-order difference equations with parameters and sign-changing nonlinearities, subject to multi-point coupled boundary conditions. In the proof of our main theorems we use the nonlinear alternative of Leray-Schauder type and the Guo-Krasnosel'skii fixed point theorem.